Structural and vibrational study of primidone based on monomer and dimer calculations - Çelik, Sefa; Kecel Gündüz, Serda; Özel, Ayşen E.; AKYÜZ, SEVİM (Taylor & Francis Inc, 530 Walnut Street, Ste 850, Philadelphia, Pa 19106 USA, 2015)
Primidone (Mysoline), with the chemical formula 5-ethyl-5-phenyl-hexahydropyrimidine- 4,6-dione (C12H14N2O2), has been a valuable drug in the treatment of epilepsy. In the present work, the experimental IR and Raman spectra of solid phase primidone were recorded, and the results were compared with theoretical wavenumber values of monomer and dimer forms of the title molecule. Vibrational spectral simulations in the dimer form were carried out to improve the assignment of the bands in the solid phase experimental spectra. The possible stable conformers of free molecule were searched by means of torsion potential energy surfaces scan studies through two dihedral angles. The molecular geometries of the monomer and dimer forms of title molecule were optimized using DFT method at B3LYP/6-31++G(d,p) level of theory. Using PEDs determined the contributions of internal (stretching, bending, etc.) coordinates to each normal mode of vibration. Further, HOMO-LUMO energy gap and NBO properties of the investigated molecule in monomer and dimer forms were also calculated.
Keywords: NBO; Raman spectra; DFT; IR; BSSE; Primidone; Ab-Initio; Crystal-Structure; Raman-Spectra; Force-Fields; Ft-Raman; Acid; Prediction; Molvib; Uracil; Drugs